The Role of Perioperative Endoscopic Retrograde Cholangiopancreatography and Biliary Drainage in Large Liver Hydatid Cysts. (9th November 2014) - Krasniqi, A.; Bicaj, B.; Limani, D.; Maxhuni, M.; Rrusta, A.; Hoxha, F.; Hamza, A.; Zejnullahu, V.; Sada, F.; Hashani, S.; Musa, R.; Latifi, R.
Abstract : Background . The best surgical technique for large liver hydatid cysts (LHCs) has not yet been agreed on. Objectives . The objective of this study was to examine the role of perioperative endoscopic retrograde cholangiopancreatography (ERCP) and biliary drainage in patients with large LHCs. Methods . A 20-year retrospective study of patients with LHCs treated surgically at the University Clinical Center of Kosovo (UCCK). We divided patients into 2 groups based on treatment period: 1981–1990 (Group I) and 2001–2010 (Group II). Demographic characteristics (sex, age), the surgical procedure performed, complications rate, and outcomes were compared. Results . Of the 340 patients in our study, 218 (64.1%) were female with median age of 37 years (range, 17 to 81 years). 71% of patients underwent endocystectomy with partial pericystectomy and omentoplication, 8% total pericystectomy, 18% endocystectomy with capitonnage, and 3% external drainage. In Group I, 10 patients underwent bile duct exploration and T-tube placement; in Group II, 39 patients underwent bile duct exploration and T-tube placement. In addition, 9 patients in Group II underwent perioperative ERCP with papillotomy. The complication rate was 14.32% versus 6.37%, respectively (P = 0.001 ). Conclusion . Perioperative ERCP and biliary drainage significantly decreased the complication rate and improved outcomes in patients with large LHCs.